HUBUNGAN POLA ASUH ORANG TUA SISWA DENGAN PERKEMBANGAN BAHASA ANAK PRASEKOLAH DI TK BUDI MULIA BANJARBARU - Anggraini, Dessy; Dwi Salmarini, Desilestia; Kusumawati, Linda (LPPM Universitas Sari Mulia, 2024)
Background: In Indonesia, the prevalence of delay in preschool is between 5% and 10%. In Budi Mulia Kindergarten, there are 19 children out of 50 children whose language development falls into the suspect category. Delays in language in preschoolers are caused by parental parenting. Purpose: Knowing about relationship between parental parenting and language development in preschoolers at Budi Mulia Banjarbaru Kindergarten. Method: This research method is analytical observational with Case Control design and sampling technique using simple random sampling technique. Data retrieval instruments using questionnaires. Results: There are still 11 parents who have authoritarian parenting (32.4%). The chi-squaretest showed a p-value of 0.028 < 0.05 so that there was a relationship between parental parenting and language development in preschoolers at Budi Mulia Banjarbaru Kindergarten. Hasil OR showed that parents who used authoritarian parenting were 8,438 times more at risk of developing language in the suspect category compared to parents with democratic parenting (95% CI 1,457-48,851). Conclusion: Based on the results of research on educating children, parents should be able to apply democratic parenting because it can reduce the risk of language development delays in preschoolers. Keywords: preschoolers, language development, parenting